A new genus and two new species of Araecerini from high elevation in the Andes with a synopsis of the tribe in South America (Coleoptera, Anthribidae, Choraginae) - Mermudes, José Ricardo M. (Zootaxa, 2015)
A new genus and two new species in the tribe Araecerini are described from South America. The new genus and species Aurigeripilus andinus gen. nov. et sp. nov. from high elevation (2930 m) from Colombia (PNN Chingaza Bosque Palacio) is described and characterized by a conspicuous antebasal carina of the pronotum. Neoxenus corrugatus sp. nov. is also described from Ecuador (Napo, Baeza). Illustrations are provided of both species. An overview with diagnostic characteres of South America genera of the tribe Araecerini Lacordaire is presented.